2010
DOI: 10.7326/0003-4819-153-2-201007200-00257
|View full text |Cite
|
Sign up to set email alerts
|

Brief Communication: Case Reports of Ribavirin Treatment for Chronic Hepatitis E

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
1
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 24 publications
3
110
1
8
Order By: Relevance
“…3,24,30,41,83,84 The clinical and laboratory features of chronic HEV in these patients are similar to those in recipients of a SOT. A few cases have been treated successfully with pegylated interferon or ribavirin as monotherapies.…”
Section: Chronic Hev Infection In Patients With a Hematological Maligsupporting
confidence: 52%
See 3 more Smart Citations
“…3,24,30,41,83,84 The clinical and laboratory features of chronic HEV in these patients are similar to those in recipients of a SOT. A few cases have been treated successfully with pegylated interferon or ribavirin as monotherapies.…”
Section: Chronic Hev Infection In Patients With a Hematological Maligsupporting
confidence: 52%
“…11,12,14,18,[36][37][38][39][40][41][42][43][44][45][46][47][48] A large multicenter retrospective study, which included 85 adult patients with a SOT (kidney-, liver-, kidney-pancreas-, islet-, heart-, and lung-transplants) showed that 34.1% had spontaneous clearance of HEV within the first 6 months after HEV was diagnosed and no HEV reactivation later on, whereas 65.9% developed chronic hepatitis. 49 Interestingly, in contrast to non-immunosuppressed patients who usually present to hospital with jaundice, 50 when HEV was diagnosed, only 32% of patients were symptomatic.…”
Section: Natural History Of Hev Infection In Patients With a Sotmentioning
confidence: 99%
See 2 more Smart Citations
“…While all three patients had undetectable HEV RNA in serum and stool at 12 wk of treatment, one patient developed acute humoral graft rejection while HEV RNA was redetected in another patient, 2 wk after completion of interferon therapy. Due to the risk of graft rejection from decreasing dose of immunosuppressive drugs and using pegylated interferon α, Mallet et al [59] studied the use of ribavirin in treating two patients with chronic hepatitis E (one was post kidney and pancreas transplant and other has idiopathic CD4 T lymphocytopenia). Both patients received ribavirin at a dose of 12 mg/kg per day for 12 wk.…”
Section: Treatment Of Chronic Hepatitis Ementioning
confidence: 99%